Optic Properties on AgGaSe2 Polycristal Fabrication - Soepardjo, A. Harsono; Janusetiawan, I Dewa Made (Makara Journal of Technology, 2004)
Optic Properties on AgGaSe2 Polycristal Fabrication. Polycristal AgGaSe2, is compound (I-III-VI2) a semiconductor as basic material for thin film for solar cell. Polycristal was succesfully grown using Bridgmann Method, heated on sequential temperature treatment until 850°C and cooled down slowly until room temperature. Results observed were in the form of ingot (bars) with more or less 3 cm length and 13 mm in diameter. By using X-Ray Fefraction, composition obtained of each element (weight %) was Ag = 29,3996 %, Ga = 36,8123 % and Se = 30,29 % while using X-Ray Difraction lattice parameter obtained/calculated a = 4,4112 Å, c = 8,8854 Å, and c/a = 2,01426.